2018
DOI: 10.1177/1368430217747406
|View full text |Cite
|
Sign up to set email alerts
|

The gendered nature of stereotypes about climate change opinion groups

Abstract: We document the gendered nature and valence of stereotypes about each of the Six Americas climate change opinion groups that represent a continuum of climate change opinions from Dismissive to Alarmed. Results primarily supported predictions. First, the more groups were associated with strong concern about climate change, the more feminine they were perceived to be. Second, groups with strong concern or strong lack of concern were seen the most negatively. However, contrary to expectations, greater concern was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 32 publications
3
24
2
Order By: Relevance
“…Attitudes and beliefs (including “pro‐environmentalism”) predictive of SC are implicitly and explicitly associated with women (Brough et al., ), and people expect women to be more concerned about environmental issues like climate change while they expect men to be dismissive (Swim & Geiger, ). Research that documents gender differences in forms of SC which follow traditional caretaking roles for women can easily be interpreted as “women are naturally more caring than men.” However, research on the socialization of gender roles and values suggests a more complicated and nuanced explanation for surface‐level findings about gender differences.…”
Section: Gendered Differences In Sc Behaviormentioning
confidence: 99%
“…Attitudes and beliefs (including “pro‐environmentalism”) predictive of SC are implicitly and explicitly associated with women (Brough et al., ), and people expect women to be more concerned about environmental issues like climate change while they expect men to be dismissive (Swim & Geiger, ). Research that documents gender differences in forms of SC which follow traditional caretaking roles for women can easily be interpreted as “women are naturally more caring than men.” However, research on the socialization of gender roles and values suggests a more complicated and nuanced explanation for surface‐level findings about gender differences.…”
Section: Gendered Differences In Sc Behaviormentioning
confidence: 99%
“…Emerging avenues of research have signaled the relevance of impressions of issue publics in guiding individuals' engagement with issues (Bashir et al, 2013;Geiger, 2018). Here we build off this previous work by explicitly considering the gendered nature of these impressions based on other work suggesting that gender is a core component of impressions of climate change issue publics (Swim and Geiger, 2018), that these gendered impressions can influence decisionmaking , and more generally, that gender is a core component of how we evaluate others (e.g., Stangor et al, 1992). Thus, these studies suggested that gendered impressions could meaningfully contribute to collective action decisions.…”
Section: Gendered Impressions Of Issue Publics As Predictors Of Climamentioning
confidence: 92%
“…First, previous research suggests a link between impressions of an issue public and interest in engaging in group-supportive behavior. More specifically, previous research suggests that many hold negative or mixed impressions of activists and the climate concerned (i.e., members of the public who are most concerned about climate change and support action to address the issue), with negativity especially pronounced when considering those who engage in collective action behavior (Bashir et al, 2013;Klas et al, 2018;Swim and Geiger, 2018). Similarly, most hold negative impressions of the climate dismissive (i.e., members of the public who are least concerned about climate change and oppose action to address the issue; Swim and Geiger, 2018).…”
Section: Impressions Of Issue Public Groups and Activismmentioning
confidence: 99%
See 1 more Smart Citation
“…When individuals are concerned with how they are perceived by others, they may alter their use or display of negative emotions (Flett et al, 1988). Negative stereotypes about environmentalists include characteristics such as "nagging" or "complaining" (Swim and Geiger, 2018) and being seen as "eccentric, " "over-reactive" and "self-righteous" (Bashir et al, 2013), while "emotional" displays may be perceived as antithetical to logic (Shields, 2013). Thus, those who are concerned about climate change may want to manage the impression they make on others by restricting their use of emotions in climate change communication.…”
Section: Emotions and Impression Managementmentioning
confidence: 99%